The Lost World of Genesis One. Ancient Cosmology and the Origins Debate, John H. Walton : book review - Meyer, Esias E. (Old Testament essays, 2011)
The motto of the publishers of this book is "Evangelically Rooted. Critically Engaged," which seems to imply that this book is written for an Evangelical audience with the purpose of exposing them to critical thinking. In that case, the motto is not a bad description of the book as a whole. The book starts off well by arguing that the Bible was not written for its modern-day readers and that the two primary stumbling blocks that modern-day readers have to overcome are language and culture. The book attempts to make a contribution towards understanding the latter in particular, given the fact that Israel was an Ancient Near Eastern culture. Walton explains to his readers that Israel was not only influenced by the ancient world, but that "they were part of that world" (p. 14).